CNS Depressant activity of ethanol extract of sterculia guttata seeds in mice - Katade, S. R.; Misar, Ashwini V.; Mujumdar, Arvind M.; Phalgune, U. D.; Wakharkar, R. D.; Deshpande, N. R. (Indian Journal of Pharmaceutical Sciences, 2009)
Shade dried, powdered seeds of Sterculia guttata were extracted using a Soxhlet extractor with ethanol. Ethanol was removed under reduced pressure and dried to obtained crude extract. This extract was evaluated for its effect on behavioral changes, exploratory activity and barbiturate-sleeping time, using appropriate standard methods in mice. The extract exhibited dose-dependent CNS depressant activity.
Keywords: Barbitone sodium; CNS depressant activity; pentobarbitone sodium; Sterculia guttata Roxb.; Swiss albino mice